2016
DOI: 10.1080/09540253.2016.1247947
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical possibilities for unruly bodies

Abstract: Project Re•Vision uses disability arts to disrupt stereotypical understandings of disability and difference that create barriers to healthcare. In this paper, we examine how digital stories produced through Re•Vision disrupt biopedagogies by working as bodybecoming pedagogies to create non-didactic possibilities for living in/with difference. We engage in meaning making about eight stories made by women and trans people living with disabilities and differences, with our interpretations guided by the following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

5
3

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 30 publications
(13 reference statements)
0
43
0
Order By: Relevance
“…In Re•Vision's first six years, we have run close to 100 storytelling workshops across Canada for diverse projects involving people with disabilities and health‐care providers on changing conceptions of disability in health care (Rice, Chandler, and Changfoot ; Rice and Mündel forthcoming; Rice et al. , , ); racialized and nonracialized youth with mental health issues, police, and mental health workers on system responses to youth with mental health issues (Ferrari, Rice, and McKenzie ); Indigenous and non‐Indigenous students, teachers, and parents on what is needed to decolonize public schools (Rice et al. ); with academics on the values underpinning, and their relationship to, their research programs (Rice et al.…”
Section: From Digital To Multimedia Story‐makingmentioning
confidence: 99%
See 1 more Smart Citation
“…In Re•Vision's first six years, we have run close to 100 storytelling workshops across Canada for diverse projects involving people with disabilities and health‐care providers on changing conceptions of disability in health care (Rice, Chandler, and Changfoot ; Rice and Mündel forthcoming; Rice et al. , , ); racialized and nonracialized youth with mental health issues, police, and mental health workers on system responses to youth with mental health issues (Ferrari, Rice, and McKenzie ); Indigenous and non‐Indigenous students, teachers, and parents on what is needed to decolonize public schools (Rice et al. ); with academics on the values underpinning, and their relationship to, their research programs (Rice et al.…”
Section: From Digital To Multimedia Story‐makingmentioning
confidence: 99%
“…Building on and apart from Brushwood Rose's psychoanalytic analysis of self‐narratives, we approach storywork from a feminist posthumanist processual perspective (Braidotti ; Rice et al. ). This view understands story‐making as potent not (only or primarily) for unearthing that which we did not previously know about ourselves (the orientation of psychoanalysis and psychology generally), but for bringing into being that which we might be coming to express and understand about our subjectivities and social identities through our ongoing encounters with the world.…”
Section: From Digital To Multimedia Story‐makingmentioning
confidence: 99%
“…Our work thus supports and initiates both professional/studio‐based and participatory/community‐based art practice and brings artists, academics, and community members together to examine the possibilities of art for knowledge‐generation, cultural creation, and social change (Rice et al. ).…”
Section: Storytelling and Curation In Feminist Disability Artsmentioning
confidence: 84%
“…By making their own self-reflexive films, researchers themselves became research participants and some also identified as members of Disability Arts communities beyond Re•Vision. As Re•Vision's work progressed, an emphasis on Disability Arts-and on incubating Disability Arts community-emerged (Chandler, Rice, Changfoot, LaMarre, Mykitiuk & Mundel, forthcoming;Rice, Chandler, Liddiard, Rinaldi, & Harrison, 2016).…”
Section: Re•visionmentioning
confidence: 99%